2017
DOI: 10.1002/14651858.cd012622
|View full text |Cite
|
Sign up to set email alerts
|

Non-pharmacological interventions for chronic pain in multiple sclerosis

Abstract: Non-pharmacological interventions for chronic pain in multiple sclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 62 publications
0
9
0
2
Order By: Relevance
“…Meanwhile, Amatya indicated that MT was significantly effective in soothing fatigue and pain. 48 Also, The Arab's study showed MT could reduce fatigue in MS patients. 1 MT, in contrast to exercise which, causes a stressful physiological condition (such as increased pulse rate and blood pressure), improves blood flow in completely relaxing conditions; it, also increases the intake of nutrients and oxygen and removes more cellular waste.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Amatya indicated that MT was significantly effective in soothing fatigue and pain. 48 Also, The Arab's study showed MT could reduce fatigue in MS patients. 1 MT, in contrast to exercise which, causes a stressful physiological condition (such as increased pulse rate and blood pressure), improves blood flow in completely relaxing conditions; it, also increases the intake of nutrients and oxygen and removes more cellular waste.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, multiple sclerosis is detected in 2-14% of the patients with TN. 12,14,48,[52][53][54][55][56][57][58][59] TN is more commonly seen in adults compared with pediatric TN, which comprises less than 1.5% of all cases. [60][61][62] Pediatric TN is more likely to be bilateral (42%) compared with adult TN.…”
Section: Epidemiologymentioning
confidence: 99%
“…Intervensi medis dapat dibagi menjadi dua, yaitu terapi farmakologis dan terapi nonfarmakologis (invasif). 9 Terapi non-farmakologis (invasif) dapat menggunakan ablasi saraf (denervasi kimiawi, krioneurolisis atau krioablasi, ablasi radiofrekuensi); injeksi blok [injeksi blok sendi, seperti sendi faset (sendi atlanto-aksial dan atlanto-oksipital) dan sendi sakroiliaka]; blok saraf dan akar saraf (seperti blok pleksus seliaka, pleksus hipogastrik, saraf simpatis lumbal, dan simpatektomi paravertebral); stimulasi saraf [neuromodulasi dengan stimulus elektrik (stimulasi saraf subkutan perifer dan medula spinalis) dan stimulasi saraf elektrik transkutaneus/ TENS]; injeksi steroid [epidural dengan/tanpa anestesi lokal, administrasi steroid pada interlaminar dan transforaminal epidural dengan atau tanpa anestesi lokal, terapi obat intratekal (blok neurolitik intratekal, injeksi non-opioid intratekal, dan injeksi opioid intratekal)]; serta invasi spinal minimal (prosedur invasi spinal minimal seperti vertebroplasti, kifoplasti dan dekompresi diskus perkutaneus). [10][11][12] Prosedur ablasi radiofrekuensi (RF) atau disebut juga rizotomi merupakan salah satu prosedur invasif minimal dengan menggunakan alat penghasil arus frekuensi tinggi yang menghasilkan panas dengan tujuan untuk membuat lesi pada suatu jaringan, termasuk jaringansaraf.…”
Section: Pembahasanunclassified